Editorial - Otsuka, Edu Teruki; Silva, Anderson Gonçalves da; Mazzari, Marcus Vinicius; Titan Júnior, Samuel de Vasconcelos (Literatura e Sociedade, 2018)
Editorial da Edição de número 25 da Revista Literatura e Sociedade